In Mermoriam: Howard Zinn August 24, 1922 - January 27, 2010 - Joyce, Davis (Teaching History: A Journal of Methods, 2010)
When I first came up with the idea of writing a book about the life and writings of Howard Zinn, I knew that writing a study of a living person could be problematic, and that at the very least I would need his cooperation, including interview time, access to papers, e-mail contact, and more. So I wrote Zinn, told him what I had in mind, and asked if he would cooperate. "Of course I'll cooperate," he replied, "otherwise, I' 11 appear in your book not merely as a radical but as a surly one." One thing few have called Howard Zinn is "surly." To the contrary, I am reminded of the comment of a secretary who had worked with Zinn at Boston University who informed me when I was doing research that "Everybody likes him!" Not everyone agreed with him, obviously, with his stand on issues or his approach to history, but most would agree that he was an incredibly nice guy. I have argued that Zinn held consistently to a "radical American vision." It was radical in the sense that it sought to bring about fundamental change in the political, economic, and social orders, to get to their roots. It was deeply American because it was grounded firmly in the ideals on which the United States was founded, the ideals of the Declaration of Independence, such ideals as life and liberty and the pursuit of happiness and equality and self-determination that are so self-evident and inherent that no government has the right to take them away. And it was a vision because, obviously, living up to those ideals is an on-going struggle, not yet a reality but a hope. Zinn realized that visions do not become reality through mere hope, that much work is required. He did his share!